We can start by simplifying the left-hand side of the equation using the identity:
cos θ (1 - cos θ) = cos θ - cos² θ
Substituting this back into the original equation, we get:
cos θ - cos² θ = sin² θ
Multiplying both sides by -1, we obtain:
cos² θ - cos θ + sin² θ = 0
Using the Pythagorean identity cos² θ + sin² θ = 1, we can simplify to:
1 - cos θ = 0
Therefore, cos θ = 1, which means that θ = 0 or θ = 2π (or any integer multiple of 2π).
However, we need to check that these values of θ satisfy the original equation.
For θ = 0, the left-hand side of the equation is 0, and the right-hand side is also 0.
For θ = 2π, the left-hand side of the equation is again 0, and the right-hand side is also 0.
Therefore, the solutions to the equation are θ = 0 and θ = 2π.
cos θ (1-cosθ) = sin θ sinθ
2 2
1 answer